The economic-political concept of Hizbut Tahrir Indonesia: reflection on the early Islamic thoughts - Nafis Irkhami (IAIN Salatiga, 2014)
Hizbut Tahrir (The Party of Liberation) is an international pan-Islamic political organization. Its goal is to unify all Muslim countries as an Islamic state(caliphate) ruled by shariah. They argued that caliphate and Islamic law shouldnot be separated. Without a caliphate, the sharia application will never betotally accomplished. Factually, these grand themes constitute the global discourseapplied by Hizbut Tahrir movements around the world. It becomesthe main idea that links their global ideological ground and commonality.Hizbut Tahrir (HT) entered into Indonesia in 1982, through M. Mustofa andAbdurrahman al-Baghdadi. As in another countries, HT got repression fromthe government. Using a momentum of the reformation era, Hizbut TahrirIndonesia (HTI) begin to socialize its ideas openly. Even in 2000, they haveregistered its organization at the Ministry of Domestic Affairs.This study aims to scrutinize the ideas of HTI thinking about political economy,which is devoted to the theory about the relationship between religion, stateand economy, as well as the construction of public finances. This study isintended as a historical study of Islamic economic thought. The discourse ofthe study focuses on three questions. First, how does HTI grow in Indonesia,and why does they flourish? Second, what are the relationship between the religion, the state and the economy according to them? Finally, how is thestructure of HTI’s public finances?This qualitative study was an exploratory-analysis. It was intended to analyzekey concepts in a plantation of thought that has been documented, bothfrom primary and secondary sources. It is a library research. The sources ofthe research are in the form of HTI’s works which have been well documentedin a large numbers, including in the Pdf formats. The study found that HTItended to see every current economic problem by reflecting it into the culturalheritage of the past. Related to this, the slogan that they have alwaysbeen shouted was “Sharia is the only solution.” From this philosophy it canbe estimated that HTI’s thoughts of Islamic public finance, will face the problemof contextualization.Hizbut Tahrir (Partai Kemerdekaan) adalah sebuah gerakan politik Islaminternasional. Tujuannya adalah untuk menjadikan negara-negara Muslim dalamsatu kepemimpinan negara Khilafah yang diatur dengan syariah. Merekaberpendapat bahwa kekhalifahan dan hukum Islam tidak dapat dipisahkan.Tanpa Negara khilafah, syariah tidak dapat diterapkan dengan sempurna.Gagasan utama inilah yang diusung oleh Hizbut Tahrir di seluruh dunia. Gagasanpokok itulah yang mempertemukan idiologi dan pergerakan mereka. HizbutTahrir masuk ke Indonesia pada tahun 1982 melalui M. Mustofa danAbdurrahman al-Bagdadi. Sebagaimana di negara-negara lain, HT mendapattekanan dari pemerintah. Dengan memanfaatkan momentum era reformasi,HTI mulai mensosialisasikan ide-idenya secara terbuka. Bahkan pada tahun2000 mereka telah mendaftarkan dirinya sebagai organisasi resmi di DepdagriDitjen Kesatuan Bangsa.Studi ini bertujuan untuk mengungkap gagasan pemikiran HTI tentangekonomi politik, khususnya mengenai teori hubungan antara agama, negaradan perekonomian, serta mengenai konstruksi keuangan publik. Kajian inidimaksudkan sebagai studi historis tentang pemikiran ekonomi Islam. Pokokmasalah dalam penelitian ini adalah: Pertama, bagaimana HTI tumbuh danberkembang di Indonesia. Kedua, bagaimanakah hubungan antara agama,Negara dan perekonomian menurut mereka. Ketiga, bagaimanakah strukturkeuangan public menurut HTI?Kajian kualitatif ini bersifat eksploratif-analisis, yakni dimaksudkan untuk mengurai dan menganalisa secara mendalam mengenai konsep-konsep kuncidalam pemikiran HTI yang telah terdokumentasikan, baik dari sumber primermaupun sekunder. Berdasar sifatnya, penelitian ini termasuk library research, dimana bahan dan sumber data penelitian ini berupa karya-karya dari tokohtokohHTI yang telah terdokumentasikan dengan baik dalam jumlah besar,termasuk dalam format Pdf. Penelitian ini menemukan bahwa HTI cenderungmelihat segala persoalan ekonomi saat ini dengan merefleksikannya pada warisanbudaya masa lalu. Terkait dengan hal ini, slogan yang selalu mereka teriakkanadalah “Syariah adalah satu-satunya solusi.” Dari cara berfikir ini dapat diperkirakanbila pemikiran-pemikiran keuangan publik HTI akan menghadapi problemkontektualitas.